THROUGH VILLAGE-OWNED BUSINESS AGENCIES, TOWARDS TOUGH TOURISM VILLAGE - Ni Kadek Poniasih; Feni Rosalia; Maulana Muklis; Tabah Maryanah (Universitas Lampung, 2022)
The development of the tourism sector is one of the efforts to improve the local and global economy by independently implementing the region's potential, including tourism management. Because the tourism and culture in Lampung province are pretty interesting, it is necessary to develop tourism into a tourist village through BUMDes. Tourism village management based on local potential necessitates community awareness and participation to constantly innovate and be creative in developing village areas that are used as tourist villages. To examine the development of ecotourism based on Village Owned Enterprises (BUMDes), especially in Lampung Province, the problem discussed in this research is how to develop ecotourism through BUMDes toward an internationally competitive tourism responsibility village. The research method used in this writing is a normative research method with a statute approach and analyzed using content analysis. The reported research demonstrates; First, the research shows that developing ecotourism through village-owned enterprises (BUMDes) to reach a tourist village can be accomplished by empowering rural communities with the goal of community welfare. BUMDes' existence can be accepted as a means of improving welfare. The presence of BUMDes in Indonesia has grown in tandem with the number of villages that comprise BUMDes. Second, tourism development can be realized through local community-based BUMDes with the participation of Pokdarwis, who previously managed tourism and whose initial capital was funded by village contributions and donations. It is a pity if a village has tourism potential and BUMDes but does not collaborate to develop a website into a tourist village. Because, in essence, Lampung Province already has culture and ecotourism that can be promoted nationally and internationally.